Neurally adjusted ventilatory assist versus conventional ventilation in the pediatric population: Are there benefits?. Issue 9 (24th June 2019) - Karikari, Serwaa; Rausa, Jacqueline; Flores, Saul; Loomba, Rohit S.
Abstract: Introduction: Neurally‐adjusted ventilator assist (NAVA) is a relatively new form of ventilation in which the electrical activity of the diaphragm is sensed by a catheter. The amplitude of this electrical signal is then used to deliver an appropriately proportioned pressure supported breath to the patient. Due to the synchronous nature of the breaths and the patient‐adjusted nature of the support, NAVA has been shown to have benefits over conventional ventilation. Meta‐analyses were conducted of published pediatric studies to compare ventilatory endpoints between NAVA and conventional ventilation. Methods: Studies comparing ventilatory parameters between NAVA and conventional ventilation in pediatric patients were identified. These studies were reviewed for appropriateness for inclusion and studies of only pediatric patients with data for similar endpoints between both arms were then pooled. Results: Statistically significant differences were noted in asynchrony, peak inspiratory pressure (PIP), and oxygen saturation by pulse oximetry. Asynchrony was 17% lower with NAVA, PIP was 1.74 cmH2 0 lower with NAVA, and oxygen saturation was 1.1% greater with NAVA. There was no statistically significant difference in peak expiratory pressure, mean airway pressure, electrical diaphragmatic activity, respiratory rate, hydrogen ion concentration, partial pressure of oxygen, or partial pressure of carbon dioxide. Conclusion: Statistically significant differences were noted in percent asynchrony, PIP, and oxygen saturation when comparing NAVA to conventional ventilation. These all tended to favor NAVA. Other than percent asynchrony, however, the other statistically significant findings were not clinically significant.